PENGARUH UKURAN PERUSAHAAN, UKURAN DEWAN KOMISARIS DAN TIPE INDUSTRI TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA PERUSAHAAN PLASTIK DAN KEMASAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2018 - M.Riduan Abdillah; Rizki Amalia Afriana; Siti Rahmah (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2020)
This research aims to examine the effect of company size, board size and industry type on the disclosure of Corporate Social Responsibility (CSR) in plastic and packaging companies listed on the Indonesia Stock Exchange in 2013-2018. The population in this research were all plastic and packaging companies listed on the Indonesia Stock Exchange during 2013-2018, totaling 84 companies. The sample in this research was obtained using a purposive sampling method. The research sample that met the criteria for the purposive sampling method was 42 plastic and packaging companies listed on the Indonesia Stock Exchange during 2013-2018. The independent variables in this research are company size, board size and type of industry, while the dependent variable in this research is the disclosure of corporate social responsibility (CSR). The results of this research find evidence that company size has no effect on disclosure of corporate social responsibility, board size has an effect on disclosure of corporate social responsibility, type of industry has no effect on disclosure of corporate social responsibility.